Perbandingan Pupuk Kompos Kotoran Sapi dan NPK Mutiara terhadap Pertumbuhan Kailan Jepang di Media Tanam Polybag - Tjang, Maximilian Edward; Dilshad Kenzie Ramadhan; Joseph Gabriel Marsidi (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2026)
Japanese kale (Brassica oleracea) is a leafy vegetable with high nutritional and economic value and strong potential for development through intensive cultivation systems, including polybag-based cultivation. Fertilization is an important factor determining plant growth success. This study aimed to analyze differences in the effects of cattle-manure compost fertilizer and NPK Mutiara fertilizer on the vegetative growth of Japanese kale, as well as to evaluate their roles in maintaining growing media fertility. The research employed a quantitative experimental approach using a single-factor Completely Randomized Design (CRD), namely fertilizer type. Treatments consisted of cattle-manure compost fertilizer and NPK Mutiara fertilizer, each with twelve replications, resulting in twenty-four experimental units. Observed parameters included plant height, leaf width, and growing media pH. The results showed that NPK Mutiara fertilizer produced better plant height and leaf width than compost fertilizer, particularly during the vegetative phase. This advantage was associated with the rapid availability of macronutrients such as nitrogen, phosphorus, and potassium for plant uptake. Meanwhile, cattle-manure compost fertilizer contributed to stabilizing growing media pH and improving soil physical and biological conditions. pH values in both treatments remained within the optimal range and did not limit plant growth. Therefore, NPK Mutiara fertilizer is more effective for short-term vegetative growth enhancement, whereas compost fertilizer supports sustainable growing media fertility.